The Influence of Financial Compensation and Non-Financial Compensation on Employee Performance - Manurung, Grace Silvia; Aprinawati, Aprinawati; Harahap, Alya Febrina; Rumahorbo, Jonathan Saputra; Angelica, Marisa; Nasution, Putri Suci Yasa; Damanik, Yogi Prasetya (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
Based on a literature review from a number of previous studies, this research aims to study how financial compensation and non-financial compensation affect employee performance. Financial compensation, which includes salary, bonuses and incentives, is considered to play a significant role in improving employee performance, while non-financial compensation, such as recognition, awards and career development, is proven to provide intrinsic satisfaction for employees. To provide a comprehensive picture, this literature review includes research that has been conducted over the last five years by examining various industrial sectors to gain a comprehensive understanding. The results of the literature analysis show that both financial and non-financial compensation have a positive effect on employee performance, although the influence of each factor can vary depending on the characteristics of the organization and type of work. This article provides guidance for management in designing effective compensation strategies to improve performance and retain quality employees.